Britain, the Cold War, and 'the importance of influencing the young': a comparison of Cyprus and Hong Kong. Issue 1 (March 2014) - Sutton, Christopher
<x xml:space="preserve">Abstract</x> This article reasserts the significance of colonial youth and imperial ideology in the cultural Cold War. It explores Britain's perceptions of colonial youth – both as its most dangerous potential enemy and as the subgroup of colonials which required the most protection against communist indoctrination – and how these shaped policy, by comparing two case studies, Cyprus and Hong Kong. Britain's tactics revealed its general understanding of the Cold War as a true total war – against an enemy from within and out and through high politics, military action, and culture – and how to win it. In the colonies, this centred largely on the differences between negative and positive policy (the former prohibited undesirable action usually through repressive legislation, while the latter provided a pro-democratic and pro-British alternative). Moreover, Britain's Cold War battles cannot be separated from its imperial aims. Its policies regarding colonial youth aimed also at pro-British state formation. Lastly, while positive, pro-democratic policies were considered to be ideal, this article argues that Britain's reliance on repression in the Cold War 'Youth Race' reflected its declining imperial power.